Human Pathogenic Practices in Ancient Egypt - Ali , Ali; Abdel Malek, Munther (Al-Adab Journal, 2024)
When we refer to human practices, we mean all the wrong actions carried out by humans, which in turn cause diseases. The ancient Egyptians believed that the occurrence of disease was a divine punishment for the sins committed by humans. If there were no sins, then evil spirits were the cause of the disease. Due to not being careful of omens or attacks by evil spirits without the knowledge of the gods, and not using appropriate spells to confront harmful magic, as well as the possibility of infection causing an evil spirit to enter the patient’s body, there was great interest in divination and dreams that indicated the possibility of diseases occurring. It has an important role in diagnosis. The inhabitants of ancient Egypt believed that if they maintained good relations with their gods, the gods would look at them with sympathy, and life on earth would continue and flourish. Therefore, they worked to please their gods, and were keen to provide that they do not make her angry, because the wrath of the gods will bring destruction to them. What is stated in (The Teachings of Anni) confirms this, as stated in the text: ((God becomes angry with those who belittle Him)).